2020
DOI: 10.1038/s41598-020-65503-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased alpha-synuclein tear fluid levels in patients with Parkinson’s disease

Abstract: The objective of the study was to estimate if altered levels of alpha-synuclein can be detected in tear fluid of patients with Parkinson’s disease (PD). Therefore, tear fluid samples of 75 PD patients, 75 control subjects and 31 atypical Parkinsonian patients were collected and analyzed in triplicates using an ultra-sensitive single molecule array (SIMOA) system and applying a human alpha-synuclein immunoassay. In PD, levels of total soluble alpha-synuclein were significantly increased compared to control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 20 publications
(25 reference statements)
0
29
0
1
Order By: Relevance
“…α‐Syn is a cytosolic protein that lacks a secretory signal peptide sequence. Previous studies have reported that α‐syn is detected in the extracellular compartments, including the cerebrospinal fluid [15,16], plasma [16,17], saliva [18], tears [19], and urine [20] in both healthy controls and patients with PD. Additionally, α‐syn exists in various forms, including monomeric, oligomeric, and phosphorylated forms [17,21].…”
Section: α‐Syn Species Are Released From the Cells Through Various Mechanismsmentioning
confidence: 99%
“…α‐Syn is a cytosolic protein that lacks a secretory signal peptide sequence. Previous studies have reported that α‐syn is detected in the extracellular compartments, including the cerebrospinal fluid [15,16], plasma [16,17], saliva [18], tears [19], and urine [20] in both healthy controls and patients with PD. Additionally, α‐syn exists in various forms, including monomeric, oligomeric, and phosphorylated forms [17,21].…”
Section: α‐Syn Species Are Released From the Cells Through Various Mechanismsmentioning
confidence: 99%
“…As the ultrasensitive methods, SMTs can contribute to driving this process. Recently, the presence of α -syn in saliva and tears has been proposed as the new potential biofluid biomarkers for PD diagnosis (Devic et al ., 2011; Maass et al ., 2020). Although their clinical feasibilities need more verification, SMTs provide the possibility to detect the low concentrations of heterogeneous amyloid aggregates.…”
Section: Application Of Smts For Amyloidosis Diagnosismentioning
confidence: 99%
“…Another study analyzed the altered level of alpha-synuclein in tear fluid obtained from 75 PD patients, 75 healthy controls, and 31 atypical Parkinsonian patients with an ultra-sensitive single-molecule array (SIMOA) system and human alpha-synuclein immunoassay. Levels of total soluble alpha-synuclein in PD were significantly increased versus control subjects (p = 0.03; area under curve (AUC) PD versus controls 0.60) [182]. Alphasynuclein could be detected and quantified in tears (small but significant differences) between PD and control subjects.…”
Section: Parkinson's Diseasementioning
confidence: 88%
“…Alphasynuclein could be detected and quantified in tears (small but significant differences) between PD and control subjects. Alpha-synuclein can be used as a promising source for further study of PD biomarker [182].…”
Section: Parkinson's Diseasementioning
confidence: 99%